Molecular prevalence of MecA and Blaz Genes with phenotypic analysis of Antibiotic Sensitivity Pattern for S.aureus Isolated From Dermal lesions of Sheep Breeders In Diyala Governorate – Iraq - Bressam Fajer, Zainab; Ibrahim Ali Al-Ezzy , Ali; H. AL-Zuhairi , Ahmed (Diyala Journal of Medicine, 2023)
Background: S. aureus is one of the dominant bacterial pathogens among dermal infections in human and animals, which have resistance to different antimicrobial drugs. Objective: Isolation and identification of S.aureus from skin lesions among sheep breeders by traditional methods, Vitek 2 system and PCR using Staur 4, 6 specific pri-mers for validation, Detection of genes (methicillin resistant (mecA), Beta- lac-tamase gene (blaZ) by conventional PCR ,determine antibiotic sensitivity pat-tern by kirby bauer disc diffusion method. Patients and Methods: A total of 44 swaps were collected from sheep breeders suffered from variety of infected skin lesions to detect methicillin sensitive and resistant s. aureus by employing traditional methods in addition to confirmatory techniques through fast rapid VETEK2 system , detection of genes (methicillin resistant (mecA), Be-ta- lactamase gene (blaZ) by conventional PCR , and determine antibiotic sensi-tivity pattern by kirby bauer disc diffusion method. Results: S.aureus was isolated from 15/44,( 34.09%) of skin lesion of sheep breeders . A total of 6/15 ,(40%) were methicillin resistant S.aureus (MRSA) ,which represent ( 13.63%) from total samples .Beta lactamase gene primers was detected in all S.aureus isolates. A 6/15,(40%) of S.aureus have resistance for members of antibiotics classes, penicillins, polypeptides, fluoroquinolones, macrolide which include the following : methicillin that was confirmed early by detection of me-cA gene , levofloxacin , ofloxacin , erythromycin and vancomycin. A 6/15,(40%) of S.aureus have multidrug resistant trait for Penicillins, Polypep-tides, Fluoroquinolones, Macrolide antibiotics. Non multidrug resistant S.aureus was reported for Penicillins (oxacillin,4/15, 26%) and Polypeptides antibiotics (vancomycin 8/15, 53.33%) of S.aureus . Absolute sensitivity was reported for gentamycin, tetracycline, rifampicin, imipenem and chloramphenicol. Conclusion: Methicillin sensitive S.aureus was more common compared with MRSA isolated from dermal infections of sheep breeders. Blaz gene was predominantly ex-pressed by S.aureus isolates followed by Mec A gene. S.aureus have resistance for penicillins, polypeptides, fluoroquinolones, macrolide which include the fol-lowing : methicillin, levofloxacin , ofloxacin , erythromycin and vancomycin . S.aureus have multidrug resistant trait for Penicillins, Polypeptides, Fluoroquin-olones, Macrolide antibiotics. S.aureus was absolutely sensitive to gentamycin, tetracycline, rifampicin, imipenem and chloramphenicol.